A coagulase-negative and non-haemolytic strain of Staphylococcus aureus for investigating the roles of SrtA in a murine model of bloodstream infection. Issue 6 (8th June 2015) - Wang, Lin; Bi, Chongwei; Wang, Tiedong; Xiang, Hua; Chen, Fuguang; Hu, Jinping; Liu, Bingrun; Cai, Hongjun; Zhong, Xiaobo; Deng, Xuming; Wang, Dacheng
Abstract : Sortase A (SrtA) is a cysteine transpeptidase and virulence factor from Staphylococcus aureus ( S. aureus ) that catalyses the attachment and display of surface proteins on the cell wall, thereby mediating bacterial adhesion to host tissues, host-cell entry and evasion of the immune response. As a result, SrtA has become an important target in the development of therapies for S. aureus infections. In this study, we used the new reference strain S. aureus Newman D2C to investigate the role of SrtA in a murine model of bloodstream infection, when the impact of coagulase and haemolysin is excluded. The results suggested that deletion of SrtA reduced the bacterial burden on the heart, liver and kidneys by blunting the host proinflammatory cytokine response at an early point in infection. Kidneys, but not heart or liver, formed abscesses on the sixth day following non-lethal infection, and this effect was diminished by SrtA mutation. These findings indicate that SrtA is a determining virulence factor in lethality and formation of renal abscesses in mice followed by S. aureus bloodstream infection. We have thus established a convenient in vitro and mouse model for developing SrtA-targeted therapeutic strategies. Abstract : The authors investigated the roles of SrtA in the pathogenesis of Staphylococcus aureus -induced lethal infection and abscess development using a new reference strain excluding the effects of coagulase and haemolysin. Abstract :